Web-Based Student Internship Attendance Application System for Effective Student Attendance Monitoring - Nurfaizi, Kelfin; Hindarto, Djarot (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2023)
The Web-Based Student Internship Attendance Application System revolutionizes the management of internship programs in higher education institutions and companies. This innovative platform addresses the critical need for a streamlined process in handling internship attendances, a vital component of higher education that equips students with essential real-world experience. Traditional methods of managing these attendances have been fraught with complexity and inefficiency. Our system introduces a user-friendly, web-based interface that enables students to record their daily attendance effortlessly using mobile devices or computers. Beyond mere attendance tracking, the system empowers students to submit detailed reports on their daily assignments and experiences. For program organizers, the system provides instantaneous access to attendance data, thereby facilitating better management and evaluation of the internship programs. Key benefits of this system include enhanced efficiency, improved accuracy, and greater transparency in attendance recording. Its capability to minimize human error in attendance tracking and to maintain a comprehensive historical record of data is invaluable for assessing program effectiveness and informing future improvements. This advancement in internship management through web technology not only enriches the student experience but also aids educational institutions and companies in optimizing their internship programs. The Web-Based Student Internship Attendance Application System represents a significant step towards modernizing and elevating the quality of internship management